If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 5 = x + -11 Reorder the terms: 5 + 9x = x + -11 Reorder the terms: 5 + 9x = -11 + x Solving 5 + 9x = -11 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 9x + -1x = -11 + x + -1x Combine like terms: 9x + -1x = 8x 5 + 8x = -11 + x + -1x Combine like terms: x + -1x = 0 5 + 8x = -11 + 0 5 + 8x = -11 Add '-5' to each side of the equation. 5 + -5 + 8x = -11 + -5 Combine like terms: 5 + -5 = 0 0 + 8x = -11 + -5 8x = -11 + -5 Combine like terms: -11 + -5 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| F(n)=5+3n | | x-.3x=434 | | 2(2y+9)=20 | | 18+18=36 | | 0,1(x-10)-0,6x=1,5x-4 | | p-(p+8)=7(p-4)+3p | | 4(x-2)=9+4x | | 1.2x-3.44= | | 6x+3=2(3x+7) | | 8x-4=3+7x | | (2X-3)(X+4)=13 | | 6=4+2y | | 81.9=33.76+9.1x | | 72+18=16(36) | | 12*6+3(18-10)+5*3-11=x | | -3x-11=3x+13 | | 8x+12=2(4x+6) | | x+38=-14 | | 12c^2-7c-10= | | 0.5(72)+0.25(36)=36 | | -7y+7=35 | | -3(x-7)=18 | | -5=6(3)-27 | | 25x^4-60c^2+36=0 | | 2/x-3=8/3x-3 | | 3=6(-5)-27 | | (12a^2b^-2)/(8a^-3b^7) | | 5x+4=x-20 | | 12a^2b^-2/8a^-3b^7 | | logx=-.29 | | a=84+2(10) | | 15n-1+5=0 |